FACTORS INFLUENCING THE OUTCOMES OF RECURRENT RETINAL DETACHMENT AFTER PARS PLANA VITRECTOMY FOR RHEGMATOGENOUS RETINAL DETACHMENT AT CIPTO MANGUNKUSUMO NATIONAL GENERAL HOSPITAL IN INDONESIA - Samsul Rizal Ziaulhak; Gitalisa Andayani Adriono; Andi Arus Victor; Ari Djatikusumo; Anggun Rama Yudantha; Mario Marbungaran Hutapea; Sita Paramita Ayuningtyas; Filza Amara Kamila Harlena (Indonesian Vitreoretinal Society, 2026)
Introduction: Recurrent retinal detachment (re-RD) after primary pars plana vitrectomy (PPV) for rhegmatogenous retinal detachment (RRD) remains a major surgical challenge with often unsatisfactory visual outcomes. This study aims to determine the incidence and identify factors influencing the anatomical and functional outcomes after surgical repair of re-RD. Methods: This retrospective, descriptive analytical study was conducted between October 2024 and December 2024 at RSUPN Cipto Mangunkusumo Hospital, Indonesia. We reviewed 368 RRD cases that underwent primary PPV between January 2022 and December 2023. Of these, 110 developed re-RD, and 72 cases that underwent at least one repair surgery were included. Detailed data on demographics, clinical status (BCVA, high myopia and lens status), and intraoperative details (number and location of tears, extent of RD, macula and proliferative vitreoretinopathy status, tamponade type, presence of choroidal detachment) were analyzed. BCVA was converted to LogMAR. Outcomes were assessed using paired t-test, Chi-square test, and multivariate logistic regression. Result: From this study, the incidence of re-RD was 29.9% (110/368). Following repair, the anatomical success rate (retina attached) was 75% (54/72). Multivariate analysis found that undergoing only one repair surgery (OR, 4.90; CI95%, 1.28–18.79; p=0.020) was the only factor significantly associated with better anatomical success. Functional outcomes improved statistically (median LogMAR 1.7 [0.5−2.3] to 1.7 [0.4−3.0]; p<0.001), but only 11.1% (8/72) of patients achieved BCVA of ≥6/60. Multivariate analysis showed macula-on status at the time of re-RD (OR 9.67; p=0.006) was the only significant predictor for better final functional outcomes. Conclusion: The anatomical and functional outcomes of re-RD management are comparable to reports from other countries. Prognosis is associated with macula status at the time of recurrence and the number of repair surgeries performed.